(untitled) (Journal of Cancer Research Updates, 2025)
Brain tumors and multiple sclerosis (MS) are complex medical conditions characterized by overlapping clinical and imaging features, posing significant challenges in accurate diagnosis. Building upon our previous work, which utilized axial MRI images for classification into three categories—normal, brain tumor, and MS—this study extends the methodology to incorporate sagittal and coronal orientations. Individual convolutional neural network (CNN) models are trained for each orientation, and their outputs are integrated using an ensemble framework with a voting mechanism. This approach leverages the complementary spatial information provided by multi-orientation analysis to enhance diagnostic precision. Experimental evaluations demonstrate that the ensemble model achieves superior classification accuracy and robustness in contrast to the single-orientation approach. This piece emphasizes the vital role that multi-orientation MRI analysis plays in mitigating diagnostic ambiguities and advancing the reliability of AI-driven medical imaging frameworks.